Short-term and long-term effects of cash for work: Evidence from a randomized controlled trial in Tunisia - Leight, Jessica; Mvukiyehe, Eric (International Food Policy Research Institute, 2023)
While a growing literature analyzes the economic effects of cash for work programs in developing countries, there remains little evidence about the longer-term effects of these interventions. This paper presents findings from a randomized controlled trial evaluating a three month intervention providing public works em ployment in rural Tunisia. The evaluation design incorporates two dimensions of randomization — community-level randomization to treatment and control, and individual-level randomization among eligible individuals — and a sample of 2,718 individuals was tracked over five years. The findings suggest that cash for work leads to significant increases in labor market engagement, assets, consumption, financial inclusion, civic engagement, psychological well being, and women’s em powerment one-year post-treatment; however, these effects have largely attenuated to zero five years post-treatment, with the exception of a positive effect on assets. There is also evidence of positive spillover effects within treatment communities, but these effects similarly attenuate over time.